Hubungan di antara dimensi personaliti, Konsep Kendiri dan pengaruh keluarga ke atas pencapaian pelajar di Rancangan Skim Felda, Johor - Azizi Hj. Yahaya; Koay, Ting Yin; Ismail Maakip; Peter Voo; Balan Rathakrishnan (2018)
The purpose of this study was to identify the relationship between the dimensions of personality, self-concept and family influence on students’ performance. The sample consists of 214 students from two secondary schools in the FELDA settlement in Johor. Random cluster sampling was employed to select participants for the study. A pilot test was conducted to assess the internal consistency of the questionnaire used in the study which was the Malay version of the Junior Eysenck Personality Inventory (JEPI) (α = .57), the Malay version of the Tennessee Self-concept Scale (α = .86) and the family influence questionnaire (α = .79). These instruments were used to examine the effects of family influence in the aspects of family cohesiveness, religious and moral aspect and freedom aspect. Pearson's Correlation was used to analyze the relationship between the dimensions of personality, self-concept and family influence. The results show a relationship between the dimensions of personality and self-concept, and between the dimensions of personality and family cohesiveness. However, there was no relationship between the dimensions of personality and the religious and moral and freedom aspect. The results also show that there was a strong relationship between self-concept and family cohesiveness and a moderate relationship between self-concept and the religious and moral aspect. However, there was no relationship between self-concept and freedom. The implications of the study were also discussed.